Hip abductors pyomyositis: a case report and review of the literature - Seyed Ali Hashemi; Amir Reza Vosoughi; Masoome Pourmokhtari (Journal of Infection in Developing Countries)
Pyomyositis, an acute hematogenous intramuscular bacterial infection, is an unusual disease in temperate climates. We present the case of a 15-year-old girl who was referred to our centre with pain, fever, and limping.  Magnetic resonance imaging and surgery showed diffuse pus collection in the hip abductor muscles. With increased incidence of this disease in immunocompromised patients in temperate areas, physicians must become familiar with its signs and symptoms to facilitate early diagnosis.